Revelations : visions, prophecy, and politics in the book of Revelation - Pagels, Elaine H., 1943- (New York : Viking, 2012)
A world-renowned scholar of religion and bestselling author of "The Gnostic Gospels, Beyond Belief," and" Reading Judas" explores the strangest and most controversial book in the Bible: the Book of Revelation.
John's Revelation : challenging the evil empire, Rome -- Visions of heaven and hell : from Ezekiel and John of Patmos to Paul -- Other revelations : heresy or illumination? -- Confronting persecution : how Jews and Christians separated politics from religion -- Constantine's conversion : how John's Revelation became part of the Bible.
Includes bibliographical references and index.
Keywords: BIBLIA N.T.; REVELACION EN LA BIBLIA; INTERPRETACION DE LA BIBLIA; ESCATOLOGIA